Modeling of kinetics of isothermal idiomorphic ferrite formation in a medium carbon vanadiumtitanium microalloyed steel - Capdevila, C.; Caballero, E. G.; García de Andrés, C. (Revista de Metalurgia, 2002)
A theoretical model is presented in this work to calculate the evolution of isothermal austenite-to-idiomorphic ferrite transformation in a medium carbon vanadium-titanium microalloyed steel. This model has been developed on the basis of the study of the nucleation and growth kinetics of idiomorphic ferrite, considering the influence of the nature, size and distribution of the inclusions, which are responsible of the intragranular nucleation of idiomorphic ferrite. Moreover, the influence of the austenite grain size on the isothermal decomposition of austenite in idiomorphic ferrite has been thoroughly analysed. An excellent agreement (85 % in R) has been obtained between experimental and predicted values of volume fraction of idiomorphic ferrite.